Pemberdayaan Literasi Dengan Wahana Saung Belajar Di Desa Jambu Timur Kabupaten Jepara - Ahmad Nurul Ikhwan; Alfina Falian Naulita Abidin; Bilal Abdul Aziz; Dinda Fara; Esa Alvina; Iswatun Hasanah; Mohammad Farhan Saputro; Muhammad Bhayu Prakoso; Nurul Faizatun Nufa; Nur Fadhilah W (Khaira Ummah, 2022)
Literacy activities must be carried out from an early age, thereby increasing the individual's desire to find out about new things that were previously unknown. So in this activity it is necessary to have a vehicle that can educate each individual. The vehicle is a vehicle for learning saung. The saung learning vehicle aims to increase the reading level of the people of East Jambu Village from all walks of life, such as from children, students to adults. The level of literacy in the current era is very low. Due to increasingly sophisticated technology, humans have been distracted by smartphones. With this learning booth, it can reduce the level of smartphone use and be more interested in reading books. The results that will be obtained in this activity: the reading level on reading readings will increase, decrease in the use of smartphones in a day, thirst for knowledge. From the learning platform programmed by the East Jambu village KKN team, the literacy level will increase.